Soil decontamination: bioremediation and phytoremediation - Nunes Cosmo, Bruno Marcos; Galeriani, Tatiani Mayara; Leoti Zanetti , Willian Aparecido (Revista Brasileira de Engenharia de Biossistemas, 2023)
Practically all agro-industrial activities and the maintenance of cities have the potential to pollute and contaminate the environment. Thus, measures to mitigate the impacts of these activities must be evaluated, including bioremediation. In this sense, this work aimed to characterize the process of soil decontamination using bioremediation and phytoremediation. To this end, a bibliographic review based on scientific articles, books, dissertations, and theses was used. Bioremediation refers to the use of living organisms to remove, reduce, or neutralize pollutants from the environment. The technique can be performed on-site (in situ) or off-site (ex situ). Plants can also be used for bioremediation, characterizing, in this case, phytoremediation. Plants for phytoremediation must show tolerance to the contaminant and the ability to absorb and metabolize it. These plants include pigeon peas, pig beans, crotalaria, vetiver grass, and others. Bioremediation is expanding, requiring further studies.